Susceptibility of Propionibacterium acnes isolated from patients with acne vulgaris to zinc ascorbate and antibiotics - Iinuma, Katsuhiro (Dove Medical Press, 2011)
PURPOSE: The in vitro antimicrobial activity of ascorbic acid derivatives against Propionibacterium acnes was tested either alone or in combination with a variety of antimicrobial agents, and their fractional inhibitory concentration index was determined using checkerboard tests. The antimicrobial effectiveness of zinc ascorbate in the treatment of acne vulgaris, either alone or in combination with antibiotics such as clindamycin that are commonly used in Japan for the treatment of acne vulgaris, was therefore examined. MATERIALS AND METHODS: The antimicrobial susceptibility of 41 strains of clindamycin-sensitive and/or clindamycin-resistant P. acnes isolated from acne vulgaris patients was tested, in comparison with a type strain of P. acnes. RESULTS: Zinc ascorbate showed antimicrobial activity against a type strain of P. acnes and its concentration (0.064%) was sufficiently lower than the normal dose (5%) of other ascorbic acid derivatives. Combinations of zinc ascorbate with clindamycin, erythromycin, and chloramphenicol showed an additive effect, and zinc ascorbate alone effectively inhibited the growth of all P. acnes including clindamycin-resistant strains. CONCLUSION: The results provide novel evidence that the combination of zinc ascorbate and clindamycin is effective for acne vulgaris treatment.